(untitled) (Journal of Engineering, 2011)
Friction stir spot welding (FSSW) is a promising solid state joining process and is widely being considered for automotive industry. In this work mechanical properties of friction stir spot welded joints were investigated for ISO(426/1CuZn10) copper alloy. The effect of main welding parameters were studied including, welding tool rotational speed, preheat time (15, 30)s , plunging time (10,30)s , dwell time 10 s ,plunging depth (0.7,0.8) mm. Group of matrices of welding parameters were used to study the effect of each parameter on properties of welded joints. Series of (FSSW) experiments were conducted using manual drilling machine. Effect of welding parameters on mechanical properties of welded joints were investigated using tensile shear test. Micro-hardness test used to indicate the changes in hardness across welding region. Based on the welding experiments conducted in this study, the results show that copper alloy (426/1CuZn10) was easy weldable using (FSSW) process with maximum failure load (420 N) at (2000 rpm) rotating speed and ( 70 s) total time for (0.5 mm) sheet thickness.